The Enigmatic Reissner’s Fiber and the Origin of Chordates - Aboitiz, Francisco; Montiel, Juan F. (Frontiers in Neuroanatomy, 2021)
Reissner’s fiber (RF) is a secreted filament that floats in the neural canal of chordates. Since its discovery in 1860, there has been no agreement on its primary function, and its strong conservation across chordate species has remained a mystery for comparative neuroanatomists. Several findings, including the chemical composition and the phylogenetic history of RF, clinical observations associating RF with the development of the neural canal, and more recent studies in zebrafish development suggesting that RF is needed to develop a straight body axis, may shed light on the functions of this structure in early chordate evolution. In this article, we will briefly review some comparative aspects of RF, its role in the maintenance of the neural canal, and the experiments on zebrafish axial development, all of which point in our view to an important role of this structure in the origin of the chordate phylum.